The Effect of Bankruptcy, Fraud, and Financial Stability on Audit Delay of Indonesian Islamic Banks Listed in Financial Services Authority From 2016-2019: English - Rizki, Luqman Aulia; Sulhani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
The gap of time between the financial report date and audited financial report date shows the time of audit done by the independent auditor, is known as audit delay. The longer the audit delay is finished, the more significant it will affect the decision making because it is one of the most factor that has large contribution in the movement of IHSG. The aim of this study is to find out whether there is or there is not a relationship between Islamic banks reporting delay to the financial determinants of bankruptcy which will be represented with z-score or Altman’s model, fraud which will be presented with M-score or Beneish’s model, and financial stability with ACHANGE as the proxy. The data used are secondary data from annual financial reports of Islamic banks in Indonesia submitted in official website of FSA or their own website, and processed using STATA application. Forty-eight samples used in this research. The result shows that the audit delay of Islamic banks in Indonesia is not affected by either bankruptcy or fraud. Meanwhile, the audit delay of Islamic banks in Indonesia is proven to be quite affected by financial stability.